Power-Law and Log-Normal Distributions in Firm Size Displacement Data - Atushi Ishikawa (Kiel Institute for the World Economy (IfW), 2008)
We have shown that firm size signed displacement data follow not only power-law in the large scale region but also the log-normal distribution in the middle scale one. In the analyses, we employ three databases: high-income data, high-sales data and positive-profits data of Japanese firms. It is particularly worth noting that the growth rate distributions of the firm size displacement have no wide tail which is observed in assets, sales of firms, the number of employees and personal income data. An extended-Gibrat's law is also found in the growth rate distributions. This leads the power-law and the log-normal distributions of the firm size displacement under the detailed balance.
Keywords: D31; D30; D39; 330; Econophysics; firm size displacement distribution; Pareto's law; log-normal distribution; (non-)Gibrat's law; detailed balance; Betriebsgrößenstruktur; Statistische Verteilung; Econophysics; Japan